Asymmetric domino heck arylation and alkylation of nonconjugated dienes : double C–F···sodium attractive noncovalent interaction - Zhu, Daoyong (2022)
Palladium catalyzes a domino Heck arylation and alkylation of nonconjugated cyclodienes to produce trans isomers of disubstituted cyclohexenes in exceptionally high enantiomeric ratios, reaching 100:1 to 200:1 in many cases. Importantly, the interactions of the two CF bonds of Josiphos and the sodium ion of malonates facilitates stereoselective allylic attack through DFT calculations and experiments. This is a new type of attractive noncovalent interactions found in organometallic catalysis.